Disruption of methicillin-resistant Staphylococcus aureus protein synthesis by tannins - Adnan S.-N.-A.; Ibrahim N.; Yaacob W.A. (European Academy of HIV/AIDS and Infectious Diseases, 2024)
Indexed by Scopus